A new record of genus Clausena Burm. F. (Rutaceae) for the flora of Vietnam - Ha, Bui Thu; Phuong, Vu Xuan (Academia Journal of Biology, 2015)
A new record of genus Clausena Burm. F. (Rutaceae) for the flora of Vietnam